A new inclusion for Bavrin's families of holomorphic functions in n-circular domains - Długosz, Renata; Leś, Edyta; Sibelska, Agnieszka (Mathematica Slovaca, 2016)
The paper concerns inclusions of Bavrin families of complex valued functions which are hololomorphic in bounded complete -circular domains and fulfil some geometric conditions. Such families were applied later to research some families of locally biholomorphic mappings in . (see for instance, J. A. Pfaltzgraff and T. J Suffridge, P. Liczberski, I. Graham and G. Kohr, H. Hamada, T. Honda, G. Kohr). Some results for functions of such families were obtained by [BAVRIN, I. I.: , Moskov Obl. Ped. Inst., Moscow, 1976 (Russian)], [DŁUGOSZ, R.: , J. Appl. Anal. (2013), 153--165], [DŁ UGOSZ, R.—LEŚ, E.: , Complex Var. Elliptic Equ. (2014), 883--899], [LEŚ-BOMBA, E.—LICZBERSKI, P.: , Demonstratio Math. (2009), 491--503], et al..